Impact of doses of protected fat supplementation on milk composition and performance of lactating Saanen goats - Rodrigo de Souza; Claudete Regina Alcalde; Júlio Cesar Damasceno; Ludmila Couto Gomes Passetti; Bruna Susan de Labio Molina; Bruna Hygino; José Augusto Horst; Geraldo Tadeu Santos (Semina: Ciências Agrárias)
This study explored the effects of protected fat supplementation on energy intake, nutrient efficiency, blood parameters, and milk production in lactating Saanen goats. Twenty multiparous goats were assigned to four diets with increasing energy levels (2.6, 2.7, 2.8, and 2.9 Mcal ME·kg⁻¹ DM), achieved by including protected fat in the diet as calcium salts of fatty acids (CSFA). Our findings revealed no impact on dry matter intake, while ether extract and total digestible nutrient intakes increased, and non-fibrous carbohydrate intake decreased linearly. Enhanced digestibility of key nutrients indicated improved overall dietary efficiency. Blood cholesterol and plasma urea levels increased in response to higher dietary energy levels. Milk production varied with the lactation phase, showing a positive and linear relationship with dietary energy initially (Y = -3.76 + 2,71X; R2=0.24) and a quadratic response from 121 days until 181 days in lactation (Y = -217.60 + 157.38X -28,03X2; R2=0.62) affecting milk fat, lactose, and protein content. Fatty acid analysis showed both linear and quadratic responses among different types, highlighting the crucial role of dietary energy in modulating the milk fatty acid profile for improved nutritional quality. Beneficial long-chain fatty acids like C18:0 and C18:3n3 increased, while short-chain and medium-chain fatty acids declined with higher energy levels. Additionally, C18:2n6c and C20:1 showed significant quadratic responses. These findings suggest the lactation phase-dependent effects of protected fat supplementation on milk production and composition, emphasizing the importance of meeting specific nutritional demands throughout lactation.